Optimization of the production process of dried unripe olives (Olea europaea L.) as a nutraceutical ingredient naturally rich in phenolic compounds. (July 2020) - Cecchi, Lorenzo; Guerrini, Lorenzo; Bellumori, Maria; Balli, Diletta; Xie, Pujun; Parenti, Alessandro; Mulinacci, Nadia
Abstract: Phenols from Olea europaea L. exert several beneficial effects on human health. Olive fruits, particularly the unripe ones, thanks to very high phenols contents (e.g. oleuropein, 80, 000 mg/kg), can become a new source of income for olive oil producers, with only a negligible reduction of olive oil production. Aim of this research was to define the best process for obtaining dried unripe green olives very rich in phenols from Olea europaea L. analyzing three typical Tuscan cultivars. Four different freezing methods and different combinations of storage times and temperatures were applied to olives before lyophilization for selecting the best procedure to preserve the native phenols. Moraiolo harvested seven-ten days before complete stone lignification showed to be the most suitable cv for production of the ingredient, with oleuropein 100 g/kg and total phenols 178 g/kg. The application of liquid nitrogen immediately followed by lyophilization gave the best results, while other approaches led to losses of oleuropein of at least 68%. As far as storage before lyophilization, the best performance was for olives frozen in liquid nitrogen kept at −80 °C, with a loss of phenols less than 20% after five months, and oleuropein contents still higher than 80, 000 mg/kg. Highlights: A correct management of unripe olives for obtaining a new ingredient rich in phenols. Moraiolo cv before stone lignification was the richest among three Tuscan varieties. Freezing with liquid N2 before freeze-drying best preserves the phenolic compounds. Phenols are well preserved over time in cold olives only if frozen with liquid N2 .